Efficacy of additional psychosocial intervention in reducing low birth weight and preterm birth in teenage pregnancy: A systematic review and meta‐analysis. (7th August 2015) - Sukhato, Kanokporn; Wongrathanandha, Chathaya; Thakkinstian, Ammarin; Dellow, Alan; Horsuwansak, Pornpot; Anothaisintawee, Thunyarat
Abstract: This systematic review aimed to assess the efficacy of psychosocial interventions in reducing risk of low birth weight (LBW) and preterm birth (PTB) in teenage pregnancy. Relevant studies were identified from Medline, Scopus, CINAHL, and CENTRAL databases. Randomized controlled trials investigating effect of psychosocial interventions on risk of LBW and PTB, compared to routine antenatal care (ANC) were eligible. Relative risks (RR) of LBW and PTB were pooled using inverse variance method. Mean differences of birth weight (BW) between intervention and control groups were pooled using unstandardized mean difference (USMD). Five studies were included in the review. Compared with routine ANC, psychosocial interventions significantly reduced risk of LBW by 40% (95%CI: 8%, 62%) but not for PTB (pooled RR = 0.67, 95%CI: 0.42, 1.05). Mean BW of the intervention group was significantly higher than that of the control group with USMD of 200.63 g (95% CI: 21.02, 380.25). Results of our study suggest that psychosocial interventions significantly reduced risk of LBW in teenage pregnancy.